2012
DOI: 10.1108/17506181211206234
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐cultural differences in purchase decision‐making criteria

Abstract: Purpose -The main purpose of this study is to draw implications about simultaneous consideration of demographics, preferences and attitudes in understanding travel behavior decision criteria.Design/methodology/approach -Convenience sampling was used to collect data. In 2006 university students in Turkey collected data from visitors at hotels. From distribution of 1,067 questionnaires, 906 usable questionnaires were collected. Data used are for Turkish (local), European and Asian tourists.Findings -One expects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…For example, the Chinese outbound tourism market is predicted to be a major force in the future (Yeoman 2008). This is important because studies show that culture influences tourists' needs, wants and expectations (Lee & Ulgado 1997, Ozdipciner et al 2012; destination image, motivation and satisfaction (Kozak et al 2003); communication style and customer satisfaction (Reisinger & Turner, 2003), as well as service delivery (Armstrong et al 1997) and service recovery (Mattila & Patterson 2004). As a result, many organisations are scrambling to gain a better understanding of the needs and wants of this cultural market segment.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Chinese outbound tourism market is predicted to be a major force in the future (Yeoman 2008). This is important because studies show that culture influences tourists' needs, wants and expectations (Lee & Ulgado 1997, Ozdipciner et al 2012; destination image, motivation and satisfaction (Kozak et al 2003); communication style and customer satisfaction (Reisinger & Turner, 2003), as well as service delivery (Armstrong et al 1997) and service recovery (Mattila & Patterson 2004). As a result, many organisations are scrambling to gain a better understanding of the needs and wants of this cultural market segment.…”
Section: Discussionmentioning
confidence: 99%
“…Armstrong et al , 1997; Sultan and Simpson, 2000; Tsaur et al 2005; McCleary et al , 2007; Torres et al , 2014), even in the latest contributions (e.g. Ozdipciner et al , 2012; Oh and Hsu, 2014). Few studies that included at least one European country in their research were mainly concerned with the UK (e.g.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Significant differences were reported particularly between western and Asian cultures in their destination choice behaviour (Kim & Lee, 2000;You, O'Leary, Morrison & Hong, 2000), and information search behaviour (Chen & Gursoy, 2000). The relationship between origin and demographics, preference and attitude variables, was shown in a study by Ozdipciner et al (2012) where the behaviour of Turkish, European, and Asian tourists was analyzed. Kozak (2002), and Kozak et al (2003) identified cultural differences in behaviour including destination image, motivation, and satisfaction while visiting Turkey and Spain.…”
Section: Literature Reviewmentioning
confidence: 99%